(untitled) (Brazilian Journal of Radiation Sciences, 2023)
Certifying professionals in radioprotection (RP), according to the requirements and qualifications established in current Brazilian legislation, ensures that procedures and practices in radiology, radiotherapy and nuclear medicine be performed based on the fundamental principles of radioprotection. However, in none of the regulations and resolutions of the country involving the use of ionizing radiation, the qualification in RP for interventional physicians, radiologists, radiotherapists, nuclear physicians, dentists, nurses and auxiliaries, specialists in medical physics, radiopharmaceuticals, technologists and technicians are clearly defined. It is necessary to adoption a certification scheme through the ABNT NBR ISO/IEC 17024:2013 standard, which will benefit the professionals themselves as well as the patients increasing the safety in RP in the country. This is to the fact that there is no harmony in the regulation of these professionals with the responsible bodies, nor uniformity in practices through international recommendations. This paper proposes the implementation of a quality management system to certify these professionals according to the principles of radiation protection through a survey of needs regarding to the certification of people and the evaluation of systems implemented in other countries.